Lila [large type] - Robinson, Marilynne (Thorndike Press, 2014)
Neglected as a toddler, Lila was rescued by a canny young drifter and together they crafted a life on the run. Despite some petty violence and moments of desperation, their life was laced with moments of joy and love. When Lila arrives in Gilead, she struggles to reconcile the life of her makeshift family and their days of hardship with the gentle Christian worldview of her husband which paradoxically judges those she loves.